An application of genetic algorithm in optimizing jeepney operations along Taft Avenue, Manila - Abad, Raymund Paolo B. (Animo Repository, 2016)
Effective transport service scheduling involves minimization of transit operating cost and maximization of generated revenue while meeting the demand for such service. This paper investigates the application of Genetic Algorithm in the optimization of Jeepney services along a busy section of their transit service routes. The main objective of this study is to improve transit service operations by minimizing travel and vehicle operating costs. The paper presented three types of services: Normal, Express A, and Express B. It was determined that a combination of the operation types would yield the smallest operating cost. Preference is still shown to Normal operation due to high passenger demand in the selected section during morning peak hours. Express services are more preferred during off-peak hours due to lower passenger demand. © 2015 IEEE.